If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 18 = -6(x + -4) Reorder the terms: 18 + -8x = -6(x + -4) Reorder the terms: 18 + -8x = -6(-4 + x) 18 + -8x = (-4 * -6 + x * -6) 18 + -8x = (24 + -6x) Solving 18 + -8x = 24 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 18 + -8x + 6x = 24 + -6x + 6x Combine like terms: -8x + 6x = -2x 18 + -2x = 24 + -6x + 6x Combine like terms: -6x + 6x = 0 18 + -2x = 24 + 0 18 + -2x = 24 Add '-18' to each side of the equation. 18 + -18 + -2x = 24 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 24 + -18 -2x = 24 + -18 Combine like terms: 24 + -18 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| 17x-4=13x+12 | | 15+7x-5=-6+8x | | x/0.35 | | b+25=80 | | 1+1=55 | | 8x-4x+(-23x)= | | 1/5x+4=10 | | Cos(2x)=.20 | | 11x/4=2x/5 | | 7x=7(6-x) | | 5x-10=4-(x-14) | | 10(x+8)=5(4x-8) | | -2.6+10.5=4.4n | | 12x+4=4(x+3) | | 15-3x-1=-x-10 | | 2x+3(3/2)=17 | | 3x+3+8x-9=7x+5 | | 2/x+8=4/x | | -4.2x+31.5=-2 | | (7y^2-2y+8)+(3y^2-3y-5)-(6y^2-6y-5)= | | 25x^2/15x | | x+11+2x-5=72 | | 1/(h+5)=1/(3(h+4)) | | y=-x+8(1)+8 | | y=2x-7(1)-7 | | g^2=9g | | 10(x+1)-5(x-2)=70 | | 45000/(X^(3/2))=120 | | 3w+4w-2=2 | | r7/5 | | 45000/X^(3/2)=120 | | 45000/L^(3/2)=120 |